2014
DOI: 10.1002/qj.2384
|View full text |Cite
|
Sign up to set email alerts
|

Use of an OSSE to evaluate background‐error covariances estimated by the NMC method

Abstract: The NMC method has proven utility for prescribing approximate background-error covariances required by variational data assimilation systems. Here, untuned NMC method estimates are compared with explicitly determined error covariances produced within an OSSE context by exploiting availability of the true simulated states. Such a comparison provides insights into what kind of rescaling is required to render the NMC method estimates usable. It is shown that rescaling of variances and directional correlation leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The NMC method was first introduced by Parrish and Derber (1992) and named after the National Meteorological Center, now called the National Centers for Environmental Prediction (NCEP). Although the method has its potential deficiencies (Errico et al 2015), it is one of the most commonly used methods for variational data assimilation. The NMC method derives the climatological BE statistics from an ensemble of the differences between forecasts of two different lengths [hereafter called the forecast difference ensemble (FDE)], but valid at the same time.…”
Section: B Derivation Of Background Error Statisticsmentioning
confidence: 99%
“…The NMC method was first introduced by Parrish and Derber (1992) and named after the National Meteorological Center, now called the National Centers for Environmental Prediction (NCEP). Although the method has its potential deficiencies (Errico et al 2015), it is one of the most commonly used methods for variational data assimilation. The NMC method derives the climatological BE statistics from an ensemble of the differences between forecasts of two different lengths [hereafter called the forecast difference ensemble (FDE)], but valid at the same time.…”
Section: B Derivation Of Background Error Statisticsmentioning
confidence: 99%
“…The values smaller than 1 such as 0.6 here are not excluded by the previous studies on forecast error growth (Lorenz 1982;Dalcher and Kalnay 1987;Reynolds et al 1994;Zagar et al 2017). Third, Errico et al (2015) showed the ratio is smaller (larger) than 1 in the extratropic (tropical) regions in their observation system simulation experiment, and we can see it would be smaller than 1 in global average from their Fig. 1.…”
Section: Discussionmentioning
confidence: 77%
“…It has been previously indicated that there are more complicated mass-wind balance relationships in the equatorial region than at higher latitudes (Zagar et al 2004;R.-C. Wang et al 2015). Thus, the NMC method does not yield good estimates for the desired background error statistics (Errico et al 2015), leading to inefficient data assimilation in the equatorial region. Therefore, it is necessary to improve the B matrix from the balancerelated and multivariate aspects, use a more complicated assimilation method, or assimilate more observations related to humidity.…”
Section: ) Impacts Of All Observations Assimilatedmentioning
confidence: 99%